The System of State Supervision Over Private Security Activities in Poland - Bogdalski, Piotr; Jarczewski, Waldemar (Internal Security, 2024)
The subject of this study is the private security sector in Poland, while the purpose of the considerations carriedout in it is the presentation and evaluation of the state system of supervision over this sector. Among the basic methods that were used to achieve the stated goal were theoretical methods, among which dogmatic-legal analysis, critical analysis of the literature and document analysis. In the introductory part of the article, the general characteristics of private security activitiesare presented, and the essence of state supervision of these activities is defined and the need for it is justified. In turn, its main part is devoted to considerations of the organisation of state supervision of the security business in Poland. In this regard, the supervisory bodies, their subject and object jurisdiction, as well as the means of control and supervision available to these bodies are presented. A summary of the findings conducted in the article is included in the final conclusions. According to them, the supervision in question has been properly placed in the subjective structure of the security system of the Polish state, while the state supervisory bodies have been equipped with means of control and supervision that are appropriate for the implementation of the tasks set for them.